2015
DOI: 10.1111/ina.12252
|View full text |Cite
|
Sign up to set email alerts
|

Can changing the timing of outdoor air intake reduce indoor concentrations of traffic‐related pollutants in schools?

Abstract: Traffic emissions have been associated with a wide range of adverse health effects. Many schools are situated close to major roads, and as children spend much of their day in school, methods to reduce traffic-related air pollutant concentrations in the school environment are warranted. One promising method to reduce pollutant concentrations in schools is to alter the timing of the ventilation so that high ventilation time periods do not correspond to rush hour traffic. Health Canada, in collaboration with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The infiltration of particles (mostly BC) from outside to inside the classroom thus seems to be higher in the morning than in the afternoon, perhaps due to window openings before the start of classes coinciding with the high traffic in the morning rush hour. MacNeill et al showed that a simple intervention such as adjusting the ventilation system to operate earlier in the morning, prior to high traffic commute periods, significantly reduced traffic‐related air pollutants (including UFP and fine particles) in schools located near major roads with heating, ventilating and air‐conditioning systems.…”
Section: Discussionmentioning
confidence: 99%
“…The infiltration of particles (mostly BC) from outside to inside the classroom thus seems to be higher in the morning than in the afternoon, perhaps due to window openings before the start of classes coinciding with the high traffic in the morning rush hour. MacNeill et al showed that a simple intervention such as adjusting the ventilation system to operate earlier in the morning, prior to high traffic commute periods, significantly reduced traffic‐related air pollutants (including UFP and fine particles) in schools located near major roads with heating, ventilating and air‐conditioning systems.…”
Section: Discussionmentioning
confidence: 99%
“…In schools, numerous investigations have reported the positive effects of increased ventilation and as such, improved IAQ on respiratory symptoms, absenteeism, test performance and long-term academic performance in school children. The proven effectiveness of air filtration systems that are built into school HVAC systems 231,232 as well as stand-alone air filtration systems in classrooms relying on natural ventilation 233 in reducing indoor pollutants of outdoor origin suggests they represent a critical mitigation measure at schools located near heavily trafficked roads, industry and other important sources of air toxics. Future research should focus on identifying the optimal technologies for removing specific indoor air pollutants (e.g.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In the present study, household income did not have a significant association with attending a school or daycare within one block of a roadway with moderate to heavy traffic, and little variation was observed between cities. Concerns over potential health effects in children and youth have led to recent investigations of possible interventions to reduce exposure to TRAP in schools (MacNeill et al 2016 , van der Zee et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%